The Role of Sensory Modulation Deficits and Behavioral Symptoms in a Diagnosis for Early Childhood - Pérez-Robles, R (2014)
To contribute to the validation of the sensory and behavioral criteria for Regulation Disorders of Sensory Processing (RDSP) (DC:0-3R, 2005), this study examined a sample of toddlers in a clinical setting to analyze: (1) the severity of sensory modulation deficits and the behavioral symptoms of RDSP; (2) the associations between sensory and behavioral symptoms; and (3) the specific role of sensory modulation deficits in an RDSP diagnosis. Based on clinical observations, 78 toddlers were classified into two groups: toddlers with RDSP (N = 18) and those with‘‘other diagnoses in Axis I/II of the DC:0-3R’’ (OD3R; N = 60). The parents completed the Infant Toddler Sensory Profile and the Achenbach Checklist. The results revealed that the RDSP group had more severe sensory modulation deficits and specific behavioral symptoms; stronger, although not significant, associations between most sensory and behavioral symptoms; and a significant sensory modulation deficit effect. These findings support the validity of RDSP.